2003
DOI: 10.1046/j.1365-2265.2003.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

Octreoscan in patients with bronchial carcinoid tumours

Abstract: Octreoscan may be used for follow-up and detection of recurrent disease in patients with somatostatin receptor-positive bronchial carcinoids. In our limited patient material, CT however, seems to be better than octreoscan for visualization of the primary tumour as well as liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 34 publications
5
46
0
3
Order By: Relevance
“…A recent study evaluating the tissue distribution of sst 2A and sst 3 in a large series (O200 cases) of pulmonary NET with clinically aggressive features (Righi et al 2010) confirmed previous data from small series, showing a decrease in the expression of sst 2 and sst 3 from lowgrade/intermediate-grade to high-grade tumors, and confirming a good correlation between immunohistochemical results and octreotide scintigraphy (Reisinger et al 1998, Granberg et al 2003, Reubi & Waser 2003.…”
Section: Sstr Expression In Endocrine Tumorssupporting
confidence: 65%
“…A recent study evaluating the tissue distribution of sst 2A and sst 3 in a large series (O200 cases) of pulmonary NET with clinically aggressive features (Righi et al 2010) confirmed previous data from small series, showing a decrease in the expression of sst 2 and sst 3 from lowgrade/intermediate-grade to high-grade tumors, and confirming a good correlation between immunohistochemical results and octreotide scintigraphy (Reisinger et al 1998, Granberg et al 2003, Reubi & Waser 2003.…”
Section: Sstr Expression In Endocrine Tumorssupporting
confidence: 65%
“…26 There is also evidence to suggest that octreotide scans are useful in occult ACTH-secreting tumors, including those of bronchial origin. [26][27][28] …”
Section: Presentationmentioning
confidence: 99%
“…They may also be imaged with octreoscan. 11 However, specificity is limited because scintigraphy is positive in many other tumours, and not all carcinoid tumours that express somatostatin receptors by immunohistochemistry test positive with octreoscan.…”
Section: Discussionmentioning
confidence: 99%